Sing down the moon - O'Dell, Scott, 1898-1989. (New York : Dell Pub. Co., 1976)
A young Navaho girl recounts the events of 1864 when her tribe was forced to march to Fort Sumner as prisoners of the white soldiers.
Reprinted by arrangement with Houghton, Mifflin.
Newbery Honor Book, 1971.
Keywords: Navajo Indians -- Fiction; Newbery Honor -- 1971.